Productive efficiency of intellectual capital-added value in large agroindustry companies - Olarte Cabana, Jairo Alberto; González González, Patricia (Cuadernos de Administración, 2022)
This paper aims to posit the Value-Added Intellectual Coefficient (VAIC) as a tool to measure the added value created from the productive efficiency of intellectual capital in large agroindustrial companies in the department of Magdalena, Colombia. To this end, value-added statements were prepared. Then, VAIC methodology-proposed indexes were determined, and finally, the association hypotheses and significant relationship between the VAIC and financial indicators were confirmed. Based on the validation of hypotheses, estimators, multiple linear regression analysis, and panel data, per the empirical results, most of the analyzed companies scored well in terms of value-added creation. Likewise, the VAIC’s solid explanatory capacity of human capital efficiency was validated concerning the values obtained in operating profit. This result confirms the assumptions of the theory of resources and capabilities.